EFFECTS OF CORNELIAN CHERRY (CORNUS MAS L.) FRUIT ON PLASMA LIPIDS, CORTISOL, T3 AND T4 LEVELS IN HAMSTERS - A. Lotfi; H. Aghdam Shahryar; H. Rasoolian (Journal of Animal and Plant Sciences, 2014)
The aim of present study was to investigate the effect of dietary cornelian cherry fruit (CCF) on plasma lipids, cortisol, T3 and T4 levels. Thirty six male hamsters were divided into four groups; Group1 (control) fed basal diet without CCF supplementation, group 2 which fed 5g CCF only at first daily meal, group3 which fed 10g CCF, at first and second daily meals and group 4 which fed 15g CCF, at first, second and third daily meals, for 20 continuous days. Dietary CCF caused significant changes in plasma total cholesterol (TC), triglyceride, high density lipoprotein-C (HDL-C) and low density lipoprotein-C (LDL-C) (P<0.01); TC and LDL-C are decreased in groups 2, 3 and 4, when compared with control (group 1), whereas triglyceride was increased in CCF supplemented groups (groups 2, 3, and 4). HDL-C was greater in groups 3 and 4, when it compared with control and group 2. The cortisol level was lower for groups 2, 3 and 4, when compared with control. But there were no any significant changes for thyroid hormones (T3 and T4) between experimental groups. It was concluded that dietary cornelian cherry fruit supplementation has hypolipidemic effect due to declining total cholesterol and LDL-C levels. Also, it can increase HDL-C (good cholesterol) and decrease cortisol level, without any considerable effect on thyroid hormones (T3 and T4) level. Dietary supplementation of cornelian cherry fruit for two meals daily is suggested to more efficient hypolipidemic effect.
Keywords: Cornelian cherry fruit; glucose; insulin; Syrian hamster